2016
DOI: 10.1007/s12668-016-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanodrug Delivery Through the Mucus Layer of Air-Liquid Interface Cultured Primary Normal Human Tracheobronchial Epithelial Cells

Abstract: Superparamagnetic iron oxide (Fe3O4) and highly anisotropic barium hexaferrite (BaFe12O19) nanoparticles were coated with an anti-inflammatory drug and magnetically transported through mucus produced by primary human airway epithelial cells. Using wet planetary ball milling, dl-2-amino-3-phosphonopropionic acid-coated BaFe12O19 nano-particles (BaNPs) of 1–100 nm in diameter were prepared in water. BaNPs and conventional 20–30-nm Fe3O4 nanoparticles (FeNPs) were then encased in a polymer (PLGA) loaded with dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…To elucidate the mechanism behind mucus penetration of loaded drugs released from NPs, ensemble-averaged geometric mean square displacements of NPs in porcine vagina tissues were defined as a function of time for such samples as the blank NPs, NPs uncoated but loaded with Nile Red, and PCN loaded with Nile Red [20,67]. As depicted in Figure 4A, the penetration rates reflected by differences in ensemble mean square displacements were examined using a quasiexperimental design [19,68].…”
Section: Ex Vivo Mucus Penetration Rates Of Npsmentioning
confidence: 99%
“…To elucidate the mechanism behind mucus penetration of loaded drugs released from NPs, ensemble-averaged geometric mean square displacements of NPs in porcine vagina tissues were defined as a function of time for such samples as the blank NPs, NPs uncoated but loaded with Nile Red, and PCN loaded with Nile Red [20,67]. As depicted in Figure 4A, the penetration rates reflected by differences in ensemble mean square displacements were examined using a quasiexperimental design [19,68].…”
Section: Ex Vivo Mucus Penetration Rates Of Npsmentioning
confidence: 99%
“…Nanoparticle systems have been previously investigated for their potential in treating asthma and other lung diseases [ 4 , 5 ]. For instance, to overcome mucus clearance and guide the therapeutics through the mucus barrier, magnetic iron oxide (Fe O ) nonaparticles [ 4 ] and barium hexaferrite (BaFe ) nanoparticles [ 6 ] have been used previously. For example, barium hexaferrite nanoparticles coated with an anti-inflammatory drug were pulled by external magnetic forces through the mucosal barrier [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, to overcome mucus clearance and guide the therapeutics through the mucus barrier, magnetic iron oxide (Fe O ) nonaparticles [ 4 ] and barium hexaferrite (BaFe ) nanoparticles [ 6 ] have been used previously. For example, barium hexaferrite nanoparticles coated with an anti-inflammatory drug were pulled by external magnetic forces through the mucosal barrier [ 6 ]. These experiments showed that barium hexaferrite nanoparticles can indeed penetrate a ∼100 m thick mucus layer in a static magnetic field gradient of 360 T/m.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations